The Cultural Significance of Football's 2006 World Cup (KULT_online, 2011)
The pivotal event of Christian Tagsold's study Spiel-Feld (Playing Field) is the 2006 World Cup of football in Germany. As a so-called Team Liaison Officer of Japan's national team, Tagsold acted as a connector between the Japanese delegation and the organizing committee of the World Cup during the events. The central question of the study is how such a multifaceted event as the World Cup, which lacks a definitive cultural interpretation, nonetheless captivates people to such a degree. By analysing symbolic exchanges, the semantics of space, and key translations, the researcher at the institute of modern East Asian studies at Heinrich Heine University Düsseldorf talks about the processes of players, workers, and fans interpreting and assigning meaning to the event. With his study he therefore contributes to a sociological understanding of football culture.